The Technology of Deception in Sergei Dovlatov’s Stories (Based on example of Certain Verbs) - GAZAROVA, DIANA (Bulletin of Yerevan University H: Russian Philology, 2021)
The paper is devoted to the ways of expression of the concept “deception” in S. Dovlatov’s works, to the comparison of theverbs “обманывать”, “лгать”, “врать” and “молчать” and their meanings in Russian linguoculture and the features of their using in Dovlatov’s stories, where lie is manifested in two forms: active and passive.
Keywords: concept “deception”, Russian linguoculture, category of default, active and passive lie, “artistic deception”